Evidence for the early clinical relevance of hallucinatory‐delusional states in the general population. (4th September 2012) - Nuevo, R.; Van Os, J.; Arango, C.; Chatterji, S.; Ayuso‐Mateos, J. L.
<x xml:space="preserve">Abstract</x> Nuevo R, Van Os J, Arango C, Chatterji S, Ayuso‐Mateos JL. Evidence for the early clinical relevance of hallucinatory‐delusional states in the general population. Objective: To analyze, in a general population sample, clustering of delusional and hallucinatory experiences in relation to environmental exposures and clinical parameters. Method: General population‐based household surveys of randomly selected adults between 18 and 65 years of age were carried out. Setting: 52 countries participating in the World Health Organization's World Health Survey were included. Participants: 225 842 subjects (55.6% women), from nationally representative samples, with an individual response rate of 98.5% within households participated. Results: Compared with isolated delusions and hallucinations, co‐occurrence of the two phenomena was associated with poorer outcome including worse general health and functioning status (OR = 0.93; 95% CI: 0.92–0.93), greater severity of symptoms (OR = 2.5 95% CI: 2.0–3.0), higher probability of lifetime diagnosis of psychotic disorder (OR = 12.9; 95% CI: 11.5–14.4), lifetime treatment for psychotic disorder (OR = 19.7; 95% CI: 17.3–22.5), and depression during the last 12 months (OR = 11.6; 95% CI: 10.9–12.4). Co‐occurrence was also associated with adversity and hearing problems (OR = 2.0; 95% CI: 1.8–2.3). Conclusion: The results suggest that the co‐occurrence of hallucinations and delusions in populations is not random but instead can be seen, compared with either phenomenon in isolation, as the result of more etiologic loading leading to a more severe clinical state.